Study on the mechanism and application of rutile flotation with benzohydroxamic acid. (April 2019) - Cao, Miao; Gao, Yude; Bu, Hao; Qiu, Xianyang
Highlights: BHA alone exhibits low collecting capacity to rutile. Lead ions effectively improve the flotation of rutile using BHA as a collector. The order of addition for lead ions and BHA affects the rutile flotation recovery. The lead ion-BHA complex improves the adsorption efficiency of BHA. Two different interaction modes of Pb 2+ and BHA with rutile are characterized. Abstract: In this study, benzohydroxamic acid (BHA) is first introduced as a collector for rutile flotation, whereas BHA alone exhibits low collecting capacity to rutile. The addition of lead ions effectively improves the flotation of rutile using BHA as a collector. The order of addition for lead ions and BHA significantly affects their interactions with the rutile surface and therefore the rutile flotation recovery. Compared to the traditional method of adding reagents in sequential order, the pre-mixed addition, which first generates lead ion–BHA complexes, improves the adsorption efficiency of BHA on the rutile surface as well as the flotation recovery. Although previous research has investigated the activation mechanism of lead ions in BHA flotation of oxide minerals, most such studies have focused on the positive effects of lead ions on BHA adsorption on the mineral surface. The present work emphasizes a new perspective, considering the adsorption behavior of lead ions on the rutile surface under different BHA collector conditions. It is shown that in the system pre-activated with lead ions, lead species are initially transferred to the rutile surface to activate it for BHA attachment; the pre-absorbed lead species undergo desorption when the BHA collector is added into the bulk solution. In addition, the desorbed lead ions in the bulk solution partly react with the BHA collector, leading to the potential adsorption of hydrophobic lead ion–BHA complexes on the rutile surfaces. However, in a binary mixed lead ion–BHA system, the lead ions react with BHA to form hydrophobic lead ion–BHA complexes at the first stage; these complexes with superior adsorption capacity are then adsorbed on the rutile surface. Visual MINTEQ simulations show that, at the optimum rutile flotation pH ∼9, this improvement is mainly attributed to the adsorption of [Pb(OH)(A)] on the rutile surfaces.